Investigation into the Total Phenols and Antioxidant Activity during Storage of Fruit Smoothies - Agbenorhevi, Jacob K.; Marshall, Lisa J. (Journal of Food Science and Engineering, 2024)
This is an article published in Journal of Food Science and Engineering 2 (2012) 72-79